A novel on-line preconcentration method for trace molybdenum determination by USN-ICP OES with biosorption on immobilized yeasts - Gil, Raul Andres; Pasini Cabello, Sergio David; Takara, Eduardo Andres; Smichowski, Patricia Nora; Olsina, Roberto Antonio; Martinez, Luis Dante (Elsevier Science, 2007)
Fil: Gil, Raul Andres. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - San Luis. Instituto de Química de San Luis. Universidad Nacional de San Luis. Facultad de Química, Bioquímica y Farmacia. Instituto de Química de San Luis; Argentina